GAYA KEPEMIMPINAN KHARISMATIK KYAI SIROJI MUSLIM ABKO DALAM MENINGKATKAN SPIRITUALITAS SANTRI PONDOK PESANTREN AL-MURABBI NIPAH KUNING - Edy Wahyudi; Syarif Ali Al Qadrie (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2023)
Leadership style is an important aspect that must be possessed by a leader in carrying out his leadership responsibilities. Leadership style is a behavior and strategy resulting from a combination of attitudes, skills, philosophy of a leader to influence the behavior of members or subordinates in an institution or organization. Leadership style is divided into several types, one of which is the charismatic leadership style. Charismatic leadership style is formed on the basis of motivational commitment and emotional identity to their vision, philosophy, and style to their members. Charismatic leaders are able to instill spiritual values ??in the emotional souls of their members, so that they are unwittingly able to create change.In this article the author conducts research on the charismatic leadership style applied by Kiyai Siroji Muslim Abko in that he is the founder and first caretaker of the Al-Murabbi Islamic boarding school which is located at Jalan Nipah Kuning Dalam, West Kalimantan. The research conducted by the author is included in the research that has just been carried out, especially in Pontianak City.Therefore, it is hoped that this article can become a reading reference which provides data on charismatic leadership so that it can be applied by readers or for leaders from an institution or organization. We hope that this article will also increase people's interest in placing their children in the Al-Murabbi Islamic boarding school, Nipah Kuning Dalam, West Kalimantan.